(untitled) (World Bulletin of Social Sciences, 2024)
The article examines and analyzes the ongoing reforms in the field of state youth policy and the priorities of state policy, their essence, necessity and significance. The role of the education system in the implementation of state youth policy and reforms implemented in this direction is comparatively analyzed.